2002
DOI: 10.1128/aem.68.8.4035-4043.2002
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Anaerobic Granules Bioaugmented with Desulfitobacterium frappieri PCP-1

Abstract: Oligonucleotide probes were used to study the structure of anaerobic granular biofilm originating from a pentachlorophenol-fed upflow anaerobic sludge bed reactor augmented with Desulfitobacterium frappieri PCP-1. Fluorescence in situ hybridization demonstrated successful colonization of anaerobic granules by strain PCP-1. Scattered microcolonies of strain PCP-1 were detected on the biofilm surface after 3 weeks of reactor operation, and a dense outer layer of strain PCP-1 was observed after 9 weeks. Hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In this respect, D. hafniense could have used chemotaxis toward pyruvate producers to scatter throughout the biofilm. We previously demonstrated that D. hafniense PCP-1 forms microcolonies and is mostly present at the surface of PCP-fed UASB reactors (27). However, in this particular case, strain PCP-1 was added to already formed granules.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In this respect, D. hafniense could have used chemotaxis toward pyruvate producers to scatter throughout the biofilm. We previously demonstrated that D. hafniense PCP-1 forms microcolonies and is mostly present at the surface of PCP-fed UASB reactors (27). However, in this particular case, strain PCP-1 was added to already formed granules.…”
Section: Discussionmentioning
confidence: 96%
“…They were then washed again in PBS for 5 min and stored at 4°C. For hybridization, biofilm samples were first dehydrated in a graded series of 50, 80, and 95% ethanol solutions for 5 min each and then soaked in an acetylation solution as described previously (27). The slides were then mounted on microscope slides for hybridization experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, exogenously grown microorganisms (pure culture or mixed culture) with known hydrolysis function may be introduced into UASB and test whether they can survive and incorporate into anaerobic granules Lanthier et al, 2002).…”
Section: Further Directionsmentioning
confidence: 99%